Punt kick motion for rugby players with different kicking skills - Arakaki, T.; Ae, M.; Shibatani, S.; Numazu, N.; Kurosaki, A.; Ito, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to compare the punt kicking motions for different kicking distances in the college and professional rugby players. Three-dimensional coordinate data were collected from nine college rugby players and six professional players. They were asked to performed three different punt kicks aiming at 35-m, 50-m and maximum (MAX) kicking distances. The approach angle varied with the kick distance in both groups. For the 35-m kick, all players used a straight approach heading to kicking direction. For the 50-m and MAX kicks, they approached to the ball diagonally, which helped to increase the hip rotation range to acquire larger swing speed.